2001
DOI: 10.4278/0890-1171-15.6.433
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Ethnically Diverse Teens in a Substance Use Prevention Advocacy Program

Abstract: Teen Activists for Community Change and Leadership Education is designed to engage high school students living in low-income neighborhoods in community advocacy efforts to transform their schools and communities so they do not reinforce use of alcohol, tobacco, and other drugs. This nine month intervention for 116 freshmen and sophomores in and near San Jose, California consisted of 30-90 minute meetings. Social cognitive constructs of sense of community, perceived self-efficacy, outcome expectancies, incentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Two studies [9,35] found that perceived self-efficacy significantly increased among youth following tobacco control advocacy activities. Youth outcome expectancy, leadership competence, and perceived policy control findings did not change significantly, similar to the present study's findings [35]. However, in a follow-up tobacco study, outcome expectancy did significantly increase, following successful advocacy activities [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies [9,35] found that perceived self-efficacy significantly increased among youth following tobacco control advocacy activities. Youth outcome expectancy, leadership competence, and perceived policy control findings did not change significantly, similar to the present study's findings [35]. However, in a follow-up tobacco study, outcome expectancy did significantly increase, following successful advocacy activities [9].…”
Section: Discussionmentioning
confidence: 99%
“…One previous tobacco advocacy study found that gender was associated with advocacy outcomes and that Black and Hispanic youth trended toward having higher advocacy readiness [35]. A high school-based youth empowerment for heart health study found that being Black (vs. White) was significantly associated with community participation [36].…”
Section: Original Researchmentioning
confidence: 97%
“…Fourth, young people tend to possess enthusiasm and optimism that can be harnessed to promote community-based changes. Winkleby et al [70] showed that youth who became involved with an advocacy program were able to enact changes in their school and community environments. Fifth, risk of obesity is highest among low-income groups and communities of color [41,47], so efforts to reduce health disparities could benefit from emphasizing youth advocacy as an additional tool.…”
Section: Rationale For Youth Advocacymentioning
confidence: 99%
“…The success of advocacy depends in part on individual attributes of advocates such as perceived incentive value, outcome expectancies, self-efficacy, perceived policy control, leadership competence, and sense of community [70]. The skills and behaviors at the core of advocacy include increased network communication, negotiation, public education, media contact, public participation, and vocalizing one's beliefs [70,72].…”
mentioning
confidence: 99%
See 1 more Smart Citation